Uji Daya Hidup Rayap Tanah (Coptotermes curvignathus Holmgren) (Isoptera : Rhinotermitidae) dalam Berbagai Media Kayu di Laboratorium - Aditia Exaudi tampubolon; Syahrial Oemry; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2015)
This research aims to determine the viability of subterranean termites (Coptotermes curvignathus Holmgren) in some media wood in laboratory. The study was conducted at Plant Pest Laboratory, Agroecotechnology Program Study, Faculty of Agriculture, University of Sumatera Utara, Medan from March to May 2014. It was done by using Completely Randomized Design (CRD) non factorial with ten treatments and three replications: control, rubber wood, jackfruit wood, mango wood, guava wood, tead, duku wood, palm wood, mahogany and guava wood. The results showed that the highest mortality in mahogany wood 8.04%. The lowest residue of wood was in mahogany 0.84 g.Keywords: Coptotermes curvignathus, mortality, wood